2021
DOI: 10.3390/microorganisms9050978
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Endophyte Diversity of Rheum palmatum from Different Production Areas in Gansu Province of China and the Association with Secondary Metabolite

Abstract: Investigations of the differences in the metabolites of medicinal plants have typically focused on the effects of external environmental factors. However, little is known about the relationship between endophytes diversity and host metabolites. We used high-throughput sequencing methods to compare the endophyte diversity of Rheum palmatum from eight different production areas in Gansu Province of China and to analyze the association between those areas and five secondary metabolites (aloe-emodin, rhein, emodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
(49 reference statements)
2
20
0
Order By: Relevance
“…It indicated that the content of loganic acid was correlated with endophytic fungi, the content of gentiopicroside, swertiamarine and sweroside were correlated with endophytic bacteria in the G. officinalis and G. siphonantha . However, Chen et al [ 3 ] and Cui et al [ 28 ] reported that that metabolites content of Rheum palmatum and Cynomorium songaricum were only correlated with endophytic fungi. Endophyte play a important role on the accumulation of secondary metabolite in medicinal plants [ 3 ], while endophyte may have different effects on the accumulation of secondary metabolites in different plants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It indicated that the content of loganic acid was correlated with endophytic fungi, the content of gentiopicroside, swertiamarine and sweroside were correlated with endophytic bacteria in the G. officinalis and G. siphonantha . However, Chen et al [ 3 ] and Cui et al [ 28 ] reported that that metabolites content of Rheum palmatum and Cynomorium songaricum were only correlated with endophytic fungi. Endophyte play a important role on the accumulation of secondary metabolite in medicinal plants [ 3 ], while endophyte may have different effects on the accumulation of secondary metabolites in different plants.…”
Section: Discussionmentioning
confidence: 99%
“…To sterilize the surface of the plant parts, the root samples were successively immersed in 70% ethanol for 5 min, 2.5% sodium hypochlorite for 1–2 min, and 70% ethanol for 1 min, and then rinsed five times with sterile Millipore water. The last portion of the washing water was inoculated in PDA (potato dextrose agar) at 28 °C for 10 d and NA (nutrient agar) at 37 °C for 3 d to validate sterilization efficiency [ 3 ]. All samples were stored at − 80 °C until DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations